SIRT5 Activation and Inorganic Phosphate Binding Reduce Cancer Cell Vitality by Modulating Autophagy/Mitophagy and ROS - Federica Barreca; Michele Aventaggiato; Laura Vitiello; Luigi Sansone; Matteo Antonio Russo; Antonello Mai; Sergio Valente; Marco Tafani (MDPI AG, 2023)
Cancer cells show increased glutamine consumption. The glutaminase (GLS) enzyme controls a limiting step in glutamine catabolism. Breast tumors, especially the triple-negative subtype, have a high expression of GLS. Our recent study demonstrated that GLS activity and ammonia production are inhibited by sirtuin 5 (SIRT5). We developed MC3138, a selective SIRT5 activator. Treatment with MC3138 mimicked the deacetylation effect mediated by SIRT5 overexpression. Moreover, GLS activity was regulated by inorganic phosphate (Pi). Considering the interconnected roles of GLS, SIRT5 and Pi in cancer growth, our hypothesis is that activation of SIRT5 and reduction in Pi could represent a valid antitumoral strategy. Treating cells with MC3138 and lanthanum acetate, a Pi chelator, decreased cell viability and clonogenicity. We also observed a modulation of MAP1LC3B and ULK1 with MC3138 and lanthanum acetate. Interestingly, inhibition of the mitophagy marker BNIP3 was observed only in the presence of MC3138. Autophagy and mitophagy modulation were accompanied by an increase in cytosolic and mitochondrial reactive oxygen species (ROS). In conclusion, our results show how SIRT5 activation and/or Pi binding can represent a valid strategy to inhibit cell proliferation by reducing glutamine metabolism and mitophagy, leading to a deleterious accumulation of ROS.